Evaluating Science Readiness of Pre-Service Elementary Teachers Through Diagnostic Assessment and Parental Feedback: Implications for Teacher Education - Avelino, Zydrick L (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to measure the science education readiness of BEEd pre-service teachers through diagnostic assessments, gather parental feedback on curriculum implementation and available resources, and identify priority areas for improvement that will enhance licensure preparation, instructional quality, and stakeholder engagement in teacher education. Methodology: The study employed a census of BEEd pre-service teachers and their parents from Bataan Peninsula State University-Bagac Campus during Academic Year 2024–2025. Data were collected through a diagnostic test aligned with the Licensure Examination for Teachers (LET) science component, structured parental questionnaires, and a 4-point Likert-scale survey. Descriptive statistics were used to analyze the diagnostic test and survey responses, while thematic analysis was applied to the qualitative parental feedback. Main Findings: The diagnostic test results showed a low mean science score of 2.68 out of 10 among BEEd pre-service teachers. Parents reported satisfaction with curriculum relevance and teaching quality but expressed concerns about the adequacy of science resources, the consistency of academic updates, and the level of school–parent communication. Thematic analysis confirmed the need for improved instructional materials, strengthened stakeholder engagement, enhanced academic support systems, and the integration of culturally responsive and technology-based approaches in science education. Novelty/Originality of this Study: This study is distinct in combining diagnostic test results with parental feedback to evaluate the readiness of BEEd pre-service teachers in science education. While earlier works have mainly focused on student performance, this research highlights the importance of parental perspectives, curriculum evaluation, and innovative approaches.